E-Government Services and the Digital Divide: A Quantitative Analysis of the Digital Divide between the General Public and Internet Users - Boksova, Jirina; Boksa, Michal; Horak, Josef; Pavlica, Karel; Strouhal, Jiri; Saroch, Stanislav (Journal of Telecommunications and the Digital Economy, 2021)
The purpose of this article is to assess the digital divide that exists between the general public and (active) Internet users in their support for the digitalization of public services (E-Government). In conducting this study, the SKODA AUTO University Research Team gathered data from 1,613 respondents – 611 respondents who are active Internet users (using computer-assisted web interviews) and 1,002 respondents from the general public (using pen-and-paper or computer-assisted personal interviews). Results have indicated that the divide exists, although it does not pose as considerable a challenge to the current E-Governance as is often assumed. Based on the current divide, improved ICT skills and higher Internet usage among citizens could increase overall support for the digitalization of public services by up to 20 percentage points. Data results also identified two societal segments, namely, respondents from 1) the age category 60+ years and 2) ‘Below-average income’ respondents, as particularly vulnerable and marginalized.